2011
DOI: 10.1103/physrevlett.106.046103
|View full text |Cite
|
Sign up to set email alerts
|

c(2×2)Water-Hydroxyl Layer on Cu(110): A Wetting Layer Stabilized by Bjerrum Defects

Abstract: Understanding the composition and stability of mixed water-hydroxyl layers is a key step in describing wetting and how surfaces respond to redox processes. Here we show that, instead of forming a complete hydrogen bonding network, structures containing an excess of water over hydroxyl are stabilized on Cu (110) by forming a distorted hexagonal network of water-hydroxyl trimers containing Bjerrum defects. This arrangement maximizes the number of strong bonds formed by water donation to OH and provides uncoordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 38 publications
4
72
2
1
Order By: Relevance
“…However, the imposed order within the adlayer dictates that relaxation occurs over long timescales. Similar hydrogen-bonding defects have been observed experimentally under ultrahigh vacuum conditions at low temperatures on Pd(111) (23) and in water-hydroxyl films on Cu(110) (24).…”
Section: Static Heterogeneity Of the Extended Metal Interfacesupporting
confidence: 63%
“…However, the imposed order within the adlayer dictates that relaxation occurs over long timescales. Similar hydrogen-bonding defects have been observed experimentally under ultrahigh vacuum conditions at low temperatures on Pd(111) (23) and in water-hydroxyl films on Cu(110) (24).…”
Section: Static Heterogeneity Of the Extended Metal Interfacesupporting
confidence: 63%
“…Fitting water-surface interaction potentials to density functional theory or higherlevel electronic structure theories is one way to take such effects into account and work in our group in this direction is ongoing [103][104][105][106] . Furthermore, it has been shown that dissociation of water molecules occurs at reactive metal surfaces so that the overlayers can be comprised of water-hydroxyl mixtures [107][108][109][110] . Taking this issue into account will require a suitable and accurate dissociable model of water.…”
Section: Future Perspective and Experimental Verificationmentioning
confidence: 99%
“…2k). Interestingly, the two inner bridging water molecules always pair up but avoid facing each other because of the repulsive force between the H atoms, forming a Bjerrum D-type defect (a crystallographic defect specific to ice, where there are two protons between the nearestneighbour pair of oxygen atoms) 12,29 . The Bjerrum D-type defect has two orthogonal orientations, which can be switched reversibly by the STM tip (Supplementary Note 2 and Supplementary Fig.…”
Section: Articlementioning
confidence: 99%
“…This hexagonal ice-like bilayer consists of a puckered hexagonal overlayer with water molecules located at two distinct heights, where the lower water molecules donate two hydrogen bonds (H bonds) to the upper layer and bond relatively strongly with the substrate, whereas the higher-lying molecules provide one donor H bond to the bottom layer and do not interact appreciably with the substrate. Recent molecular-level studies on water/metal interfaces reveal that water is distorted from the conventional bilayer-like arrangement and exhibits remarkably rich H-bonded structures arising from a subtle balance between the water-water and water-metal interactions [2][3][4][5][6][7][8][9][10][11][12][13] . Therefore, the validity of the hexagonal bilayer model on interfacial water is being challenged 13 .…”
mentioning
confidence: 99%